CHANGES OF PROTEASE INHIBITOR SYSTEM IN LUNGS UNDER CONDITION OF DEVELOPMENT OF THE EXPERIMENTAL PNEUMONIA AND ENDOMETRITIS - Ковалишин, О.А. (World of Medicine and Biology, 2015)
The objective of our research was determination of the role of functional changes of protease inhibitor system in lungs under condition of progressive EP and acute EE.Materials and Methods. Experiments were conducted on 64 guinea pigs-females with body weight between 0,20…0,24kg, which before and after the experiment were fed according to the Ration schedule for animals of vivarium of LNMU. The animals were divided into 4 groups, 16 in each group. First control group (intact), second - guinea pigs-females with EP and EE on the day 3, third – animals on the 7th day ,fourth – animals on the 14th day of the disease. Experiment was divided into two periods: the early period – the group on the 3d day of EP and EE, and the later period – animals on the days 7,14. The EP was modelled using the method of V.N.Shlyapnikov, T.L.Solodov, A.S.Stepanov. After 24 hours the EE was modelled using the instruction “The method of modelling of limited Staphilococcus aureus endometritis”. Each day such indexes were observed: general condition and behavior of animals, postoperative condition of the surgery cut, dynamics of weight. After all the animals were decapitated using the method of biological and medical researches according to the European Convention. Euthanasia was conducted using ether anaesthesia on the days 3,7 and 14; pulmonary tissue was taken for the biochemical studies; the abdominal cavity was examined. During the experiment the activity of alpha-1-proteinase inhibitor (α1-PI), alpha-2-macroglobulin (α2-M) was determined using the method of K.N.Veremeenko,O.P.Holoborodko,1988. Statistical processing of described digital data was conducted using the Stjudent method.Research Results and Discussion. Experimental researches of protease inhibitor system in lungs in the early period of the disease showed the significant growth of such indicators: azoalbumine by 32,5%(p
Keywords: protease inhibitor system; endometritis; experimental pneumonia